PERTUMBUHAN DAN PRODUKSI MICROGREENS PAKCOY PADA JENIS MEDIA TANAM DAN PUPUK ORGANIK CAIR URIN SAPI - Syamsia, Syamsia; Haslinda, Haslinda; Idhan, Abubakar (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2024)
Plant media and nutrition are key faktors in plant growth, including pakchoy microgreens. This research aims to determine the effect of the type of planting media and the dose of cow urine liquid organic fertilizer on the growth of pachoy microgreens. This research was structured using a factorial Randomized Group Design (RGD). The first factor is that the planting media consists of 3 levels, namely: cocopeat (M1), husk charcoal (M2) and cocopeat + husk charcoal (M3). The second factor is the dose of liquid organic fertilizer from cow urine cinsisting of 2 levels, namely a doses of 25 ml/L (D1), 50 ml/L (D2) and a control using water (D0). The research results show that media treatment and liquid organic fertilizer had a significant effect on the fresh weight to microgreens, but had No. significant effect on germination time, emergence of cotyledons and 100% germination. The use of cocopeat media without the applicaation of liquid organic ferlitizwer gave a better response compared to the application of liquid organic fertilizer. Husk charcoal medai, mixed media of husk charcoal and cocopeat with the aplication of 25 ml/L liquid organic fertilizer gave a better response than without the application of liquid organic fertilizer. The use of cocopeat media shoud not be accompanied by the application of liquid organic fertilizer.